Faith, violence, and phronesis: narrative identity, rhetorical symbolism, and ritual embodiment in religious communities - Gschwandtner, Christina M. (Continental philosophy review, 2020)
This contribution explores the question to what extent religious narratives can move the adherents of religious communities to violence or teach wisdom and compassion, drawing on Ricoeur’s work on narrative, ethics, and biblical interpretation. It lays out Ricoeur’s account of narrative identity, urging him to connect his account of phronesis more fully with his analysis of threefold mimesis in his earlier work. It considers his biblical hermeneutics in light of this work on identity and moral action and suggests that bringing these various dimensions of his work together more fully than he himself does would provide a more substantive account of how identity is shaped in religious contexts. It might on the one hand help us to understand more fully a turn to fundamentalism or religious violence and on the other hand draw more clearly on the phronetic resources within religious traditions, especially as they are expressed in ritual behavior, to combat violence and teach wisdom and compassion.